High-entropy alloy nitride film layer and preparation method and application thereof

The high-entropy alloy nitride film layer is prepared by magnetron sputtering technology under a nitrogen-containing atmosphere, and the problems of complex process, low preparation efficiency, and insufficient hardness and toughness in the prior art are solved, and the film layer preparation of high-hardness and high toughness is achieved.

CN119530710APending Publication Date: 2025-02-28上海工具厂有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411732116.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing high-entropy nitrogen alloy films have complex processes, low production efficiency, and insufficient hardness and toughness.

Method used

A high-entropy alloy nitride film layer was prepared by magnetron sputtering technology under a nitrogen-containing atmosphere, and the nitrogen flow rate was controlled not more than 35 sccm, and the ratio of nitrogen and argon was adjusted to optimize the film layer structure.

Benefits of technology

It has achieved high entropy alloy nitride film layer with high hardness (18~22GPa) and high fracture toughness (1.50~1.90MPa·m1/2). It has simple process and high preparation efficiency. It is suitable for protective coatings for medical devices and other components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530710A_ABST
    Figure CN119530710A_ABST
Patent Text Reader

Abstract

The invention provides a high-entropy alloy nitride film as well as a preparation method and application thereof, and belongs to the technical field of hard protective coatings. The preparation method of the high-entropy alloy nitride film layer, provided by the invention, comprises the following steps: preparing the high-entropy alloy nitride film layer on the surface of a substrate in a nitrogen-containing atmosphere by adopting a magnetron sputtering mode on the basis of a TiAlCrZrWV alloy target material; the flow of nitrogen in the nitrogen-containing atmosphere does not exceed 35 sccm. The high-entropy alloy nitride film layer can be applied to the surfaces of parts serving under frictional wear and toughness conditions such as medical instruments, so that the surface mechanical property of the parts is improved, and the service life of the parts is prolonged. In addition, the preparation method of the high-entropy alloy nitride film layer has the advantages of being simple in process, high in deposition speed, low in cost, good in mechanical property when being combined with a substrate, free of pollution to the environment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hard protective coatings, and specifically relates to a high entropy alloy nitride film layer and a preparation method and application thereof. Background Art

[0002] Compared with traditional alloys, high entropy alloys, also known as multi-principal element alloys, are alloys composed of five or more metal elements or non-metal elements in equal or nearly equal atomic ratios. Due to the high entropy effect, high entropy alloys not only do not form a large number of intermetallic compounds after solidification, but present a simple face-centered cubic (FCC) or body-centered cubic (BCC) crystal phase, or present two phases in ordinary alloys, such as eutectic high entropy alloys (EHEA).

[0003] In recent years, high entropy nitride alloy films have attracted more and more attention due to their excellent mechanical properties. Sha et al. prepared FeMnNiCoCr nitride films by DC magnetron sputtering. However, the existing high entropy nitride alloy films not only have complex processes and low preparation efficiency, but also still have the disadvantages of insufficient hardness and toughness. Summary of the invention

[0004] The purpose of the present invention is to provide a high entropy alloy nitride film layer and its preparation method and application. The high entropy alloy nitride film layer provided by the present invention has high hardness and high toughness, simple process and high preparation efficiency, which effectively solves the problems existing in the prior art.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a high entropy alloy nitride film layer, comprising the following steps:

[0007] Based on TiAlCrZrWV alloy target, a high entropy alloy nitride film layer was prepared on the substrate surface by magnetron sputtering in a nitrogen atmosphere.

[0008] The flow rate of nitrogen in the nitrogen-containing atmosphere does not exceed 35 sccm.

[0009] Preferably, the nitrogen-containing atmosphere is a mixed gas consisting of nitrogen and an inert gas; the flow ratio of nitrogen to argon in the mixed gas is 0 to 35:25.

[0010] Preferably, the flow ratio of nitrogen to argon in the mixed gas is 0:25, 5:25, 10:25, 15:25, 20:25, 25:25, 30:25 or 35:25.

[0011] Preferably, the molar ratio of each element in the TiAlCrZrWV alloy target is: Ti:Al:Cr:Zr:W:V=1:1:1:1:1:1.

[0012] Preferably, the substrate includes a metal substrate, a cemented carbide substrate, a ceramic substrate or a single crystal silicon substrate.

[0013] Preferably, the TiAlCrZrWV alloy target is a DC target; the sputtering power of the magnetron sputtering is 120-190 W, the gas pressure is 0.3-1 Pa, and the deposition time is 30-90 min.

[0014] Preferably, before preparing the high entropy alloy nitride film layer on the surface of the substrate, the substrate is subjected to ultrasonic treatment and plasma treatment in sequence.

[0015] Preferably, the reagent used for the ultrasonic treatment includes at least one of anhydrous ethanol and acetone; the frequency of the ultrasonic treatment is 15 to 30 kHz, and the time is 10 to 20 min; the plasma treatment is carried out under an argon atmosphere, and the conditions include: the DC power supply power is 120 to 190 W, the vacuum degree is 2 to 4 Pa, and the time is 5 to 15 min.

[0016] The present invention provides a high entropy alloy nitride film layer obtained by the preparation method described in the above technical solution, with a hardness of 18 to 22 GPa and a fracture toughness of 1.50 to 1.90 MPa·m 1 / 2 .

[0017] The present invention provides the application of the high entropy alloy nitride film layer described in the above technical solution in an equipment protective coating.

[0018] The present invention provides a method for preparing a high entropy alloy nitride film layer, comprising the following steps: based on a TiAlCrZrWV alloy target, a high entropy alloy nitride film layer is prepared on a substrate surface by magnetron sputtering in a nitrogen-containing atmosphere; the flow rate of nitrogen in the nitrogen-containing atmosphere does not exceed 35 sccm. The high entropy alloy nitride film layer of the present invention can be used on the surface of components that serve under friction, wear and toughness conditions such as medical equipment, thereby improving their surface mechanical properties and service life. Moreover, the method for preparing the high entropy alloy nitride film layer of the present invention has the characteristics of simple process, fast deposition speed, low cost, good mechanical properties combined with the substrate, and no pollution to the environment.

[0019] Furthermore, the nitrogen-containing atmosphere of the present invention is a mixed gas composed of nitrogen and an inert gas; the flow ratio of nitrogen to argon in the mixed gas is 0:25, 5:25, 10:25, 15:25, 20:25, 25:25, 30:25 or 35:25. In the present invention, as the nitrogen flow rate increases, the structure of the obtained high entropy alloy nitride film layer changes from an amorphous structure to a nanocomposite structure, and many interfaces of the nanocomposite structure will hinder the expansion of cracks, and finally the crack extension length is significantly shortened, showing the best anti-crack effect, and the fracture toughness of the film is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0021] Figure 1 High entropy alloy nitride film (TiAlCrZrWV) obtained under different N2 and Ar flow ratios x The deposition rate result diagram of

[0022] Figure 2 High entropy alloy nitride film (TiAlCrZrWV) obtained under different N2 and Ar flow ratios x Element change result diagram;

[0023] Figure 3 High entropy alloy nitride film (TiAlCrZrWV) obtained under different N2 and Ar flow ratios x XRD diffraction spectrum of

[0024] Figure 4 High entropy alloy nitride film (TiAlCrZrWV) obtained under different N2 and Ar flow ratios x Cross-sectional SEM morphology of

[0025] Figure 5 The high entropy alloy nitride film (TiAlCrZrWV) obtained in Example 7 x HRTEM cross-sectional morphology;

[0026] Figure 6 High entropy alloy nitride film (TiAlCrZrWV) obtained under different N2 and Ar flow ratios x The hardness and elastic modulus result diagram;

[0027] Figure 7High entropy alloy nitride film (TiAlCrZrWV) obtained under different N2 and Ar flow ratios x Fracture toughness results diagram. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing a high entropy alloy nitride film layer, comprising the following steps:

[0029] Based on TiAlCrZrWV alloy target, a high entropy alloy nitride film layer was prepared on the substrate surface by magnetron sputtering in a nitrogen atmosphere.

[0030] The flow rate of nitrogen in the nitrogen-containing atmosphere does not exceed 35 sccm.

[0031] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.

[0032] In the present invention, the substrate may include a metal substrate, a cemented carbide substrate, a ceramic substrate or a single crystal silicon substrate.

[0033] In the present invention, before preparing the template layer on the surface of the substrate, the substrate is subjected to ultrasonic treatment and plasma treatment in sequence.

[0034] In the present invention, the reagent used for the ultrasonic treatment may include at least one of anhydrous ethanol and acetone; in a specific embodiment of the present invention, the reagent used for the ultrasonic treatment is anhydrous ethanol. The frequency of the ultrasonic treatment in the present invention may be 15 to 30 kHz; in a specific embodiment of the present invention, the frequency of the ultrasonic treatment is 15 kHz, 20 kHz, 25 kHz or 30 kHz. In the present invention, the time of the ultrasonic treatment may be 10 to 20 minutes; in a specific embodiment of the present invention, the time of the ultrasonic treatment is 15 minutes.

[0035] In the present invention, the plasma treatment can be carried out in an argon atmosphere, and the flow rate of the argon gas can be 30 to 40 sccm. In the present invention, the conditions of the plasma treatment include: the DC power can be 120 to 190 W, the vacuum degree can be 2 to 4 Pa, and the time can be 5 to 15 min. In a specific embodiment of the present invention, the DC power is 180 W, and the plasma treatment time is 10 min. In a specific embodiment of the present invention, the ultrasonically treated substrate is placed in a vacuum chamber, and the vacuum chamber is evacuated to 4×10 -3 After 200 Å, argon gas is introduced to maintain the vacuum degree at 2-4 Pa, and the substrate is bombarded with argon ions. In the present invention, the plasma treatment is used to clean the surface of the substrate to facilitate the subsequent bonding of the high entropy alloy nitride film layer with the substrate.

[0036] In the present invention, the nitrogen-containing atmosphere can be a mixed gas composed of nitrogen and an inert gas. In the mixed gas of the present invention, the flow ratio of nitrogen and argon can be 0 to 35:25; in a specific embodiment of the present invention, the flow ratio of nitrogen and argon in the mixed gas is 0:25, 5:25, 10:25, 15:25, 20:25, 25:25, 30:25 or 35:25. In the present invention, with the increase of nitrogen flow rate, the structure of the obtained high entropy alloy nitride film layer changes from an amorphous structure to a nanocomposite structure, and many interfaces of the nanocomposite structure will hinder the expansion of cracks, and finally the crack extension length is significantly shortened, showing the best anti-crack effect, and the fracture toughness of the film is significantly improved.

[0037] In the present invention, the molar ratio of each element in the TiAlCrZrWV alloy target can be: Ti:Al:Cr:Zr:W:V=1:1:1:1:1:1.

[0038] After the plasma treatment, the present invention uses magnetron sputtering to prepare a high entropy alloy nitride film layer on the surface of the substrate based on the TiAlCrZrWV alloy target in a nitrogen-containing atmosphere. In a specific embodiment of the present invention, before performing the magnetron sputtering, the chamber used for the magnetron sputtering is evacuated to less than 4×10 -3 Pa. In the present invention, the TiAlCrZrWV alloy target can be a DC target. The sputtering power of the magnetron sputtering of the present invention can be 120-190W, the gas pressure can be 0.3-1Pa, and the deposition time can be 30-90min. In a specific embodiment of the present invention, the sputtering power of the magnetron sputtering is 180W, the gas pressure is 0.5Pa, and the deposition time is 60min.

[0039] The present invention obtains a high-hardness and high-toughness T high-entropy alloy nitride film layer by magnetron sputtering technology, and finally obtains a high-hardness and high-toughness TiAlCrZrWV multi-component nitride coating with different nitrogen flow rates by adjusting the ratio of argon and nitrogen. The obtained film has a dense structure, uniform thickness and excellent mechanical properties.

[0040] The present invention also provides a high entropy alloy nitride film layer obtained by the preparation method described in the above technical solution. In the present invention, the composition of the high entropy alloy nitride film layer can be (TiAlCrZrWV)N x The hardness of the high entropy alloy nitride film layer of the present invention is 18-22GPa, and the fracture toughness is 1.50-1.90MPa·m 1 / 2 In a specific embodiment of the present invention, the hardness of the high entropy alloy nitride film layer is 19.0 GPa; the fracture toughness is 1.68 MPa·m 1 / 2 .

[0041] The present invention also provides the use of the high entropy alloy nitride film layer described in the above technical solution in an equipment protective coating.

[0042] The high entropy alloy nitride film layer of the present invention can be used on the surface of components that serve under friction, wear and toughness conditions such as medical devices to be prepared into device protective coatings, thereby improving their surface mechanical properties and service life.

[0043] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The instrument specifications used in the present invention are as follows:

[0045] JGP-450 magnetron sputtering system, Shenyang Scientific Instrument Research and Development Center Co., Ltd., Chinese Academy of Sciences

[0046] D8 Advance X-ray diffractometer, Bruker, Germany

[0047] Quanta FEG450 scanning electron microscope, FEI Company, USA

[0048] BrukerTI-980 nanoindenter, Bruker, Germany

[0049] JXA-8530F PLUS field emission electron probe microanalyzer, JEOL, Japan

[0050] Tecnai G220 high-resolution transmission electron microscope, FEI Company, USA

[0051] Example 1

[0052] (1) The single crystal silicon substrate was polished, and then placed in anhydrous ethanol and washed for 15 min at 20 kHz. The washed single crystal silicon substrate was then placed in a sample chamber equipped with a TiAlCrZrWV alloy target, and the sample chamber was evacuated to 5×10 -3 Pa, argon gas was introduced to maintain the vacuum degree at 2-4 Pa, and the single crystal silicon substrate was bombarded with argon ions for 10 minutes under the condition of a DC power supply (power of 180 W).

[0053] (2) Evacuate the above chamber to a vacuum of less than 4×10 -3Pa, and argon gas (flow rate of 25sccm) was introduced into it. The TiAlCrZrWV alloy target (DC target) with equal molar ratio was opened, and a single-layer template layer was prepared by magnetron sputtering. The specific process parameters are as follows: DC sputtering power is 180W, gas pressure is 0.5Pa, and deposition time is 60min. After completion, a high entropy alloy nitride film layer (TiAlCrZrWV) N was prepared on the surface of the single crystal silicon substrate. x .

[0054] Example 2

[0055] According to the conditions of Example 1, a high entropy alloy nitride film (TiAlCrZrWV) N was prepared. x The difference is that the gas used for magnetron sputtering is adjusted to a mixed gas consisting of argon and nitrogen, wherein the flow rate of argon is 25 sccm and the flow rate of nitrogen is 5 sccm.

[0056] Example 3

[0057] According to the conditions of Example 1, a high entropy alloy nitride film (TiAlCrZrWV) N was prepared. x The difference is that the gas used for magnetron sputtering is adjusted to a mixed gas consisting of argon and nitrogen, wherein the flow rate of argon is 25 sccm and the flow rate of nitrogen is 10 sccm.

[0058] Example 4

[0059] According to the conditions of Example 1, a high entropy alloy nitride film (TiAlCrZrWV) N was prepared. x The difference is that the gas used for magnetron sputtering is adjusted to a mixed gas consisting of argon and nitrogen, wherein the flow rate of argon is 25 sccm and the flow rate of nitrogen is 15 sccm.

[0060] Example 5

[0061] According to the conditions of Example 1, a high entropy alloy nitride film (TiAlCrZrWV) N was prepared. x The difference is that the gas used for magnetron sputtering is adjusted to a mixed gas consisting of argon and nitrogen, wherein the flow rate of argon is 25 sccm and the flow rate of nitrogen is 20 sccm.

[0062] Example 6

[0063] According to the conditions of Example 1, a high entropy alloy nitride film (TiAlCrZrWV) N was prepared. x The difference is that the gas used for magnetron sputtering is adjusted to a mixed gas consisting of argon and nitrogen, wherein the flow rate of argon is 25 sccm and the flow rate of nitrogen is 25 sccm.

[0064] Example 7

[0065] According to the conditions of Example 1, a high entropy alloy nitride film (TiAlCrZrWV) N was prepared. x The difference is that the gas used for magnetron sputtering is adjusted to a mixed gas consisting of argon and nitrogen, wherein the flow rate of argon is 25 sccm and the flow rate of nitrogen is 30 sccm.

[0066] Example 8

[0067] According to the conditions of Example 1, a high entropy alloy nitride film (TiAlCrZrWV) N was prepared. x The difference is that the gas used for magnetron sputtering is adjusted to a mixed gas consisting of argon and nitrogen, wherein the flow rate of argon is 25 sccm and the flow rate of nitrogen is 35 sccm.

[0068] Test Example 1

[0069] The high entropy alloy nitride film layers (TiAlCrZrWV) N obtained in Examples 1 to 8 were respectively x The deposition rate is calculated, and the results are as follows Figure 1 shown.

[0070] Depend on Figure 1 It can be seen that with the gradual increase of the N2:Ar flow ratio, the sputtering rate of the high entropy alloy nitride film layer drops sharply from 84.59nm / min to 26.16nm / min. With the continuous increase of the N2:Ar flow ratio, the sputtering rate continues to decrease. The reasons for the decrease in the sputtering rate of the high entropy alloy nitride film layer are as follows: First, the high nitrogen flow rate will cause target poisoning, thereby reducing the deposition rate of the high entropy alloy nitride film layer. Secondly, with the continued increase of the N2:Ar flow ratio, the probability of collision between argon ions and nitrogen when impacting the target will also increase, causing the energy of the argon ions to gradually decrease, resulting in a decrease in the deposition rate of the high entropy alloy nitride film layer.

[0071] Test Example 2

[0072] The high entropy alloy nitride film layers (TiAlCrZrWV) N obtained in Examples 1 to 8 were respectively x The element content was determined and the results were as follows Figure 2 shown.

[0073] Depend on Figure 2It can be seen that when N2:Ar=0:25 (flow ratio), the content of elements in the high entropy alloy nitride film (TiAlCrZrWV) Nx is between 8.26at.% and 32.61at.%, which meets the definition of high entropy alloy. Among them, there are differences in the content of each element, mainly because the sputtering of different elements by argon ions is different. As the N2:Ar flow ratio increases, the nitrogen content in the film first increases rapidly and then tends to stabilize. Because the bond energy between Me and N is greater than the bond energy between Me and Me, Me is more likely to combine with N to form MeN, which ultimately makes the film more inclined to form a solid solution structure. When the nitrogen content continues to increase, N will dissolve into the lattice of the film. Therefore, when the N2:Ar flow ratio is greater than 20:25, the nitrogen content of the film increases slightly.

[0074] Test Example 3

[0075] The high entropy alloy nitride film layers (TiAlCrZrWV) N obtained in Examples 1 to 8 were respectively x XRD test was performed, and the results were as follows Figure 3 shown.

[0076] Depend on Figure 3 It can be seen that when N:Ar=0:25, the high entropy alloy nitride film has a wider diffraction peak, indicating that the film is amorphous at this time. The high entropy effect and the lattice distortion effect caused by the large atomic size difference together lead to the amorphous state of the film. With the increase of the N2:Ar flow ratio, the diffraction peak of the film increases, and the crystallinity of the film gradually increases. And it can be seen that the (200) diffraction peak is a preferred orientation, which indicates that the high entropy alloy nitride film is composed of a solid solution of FCC structure. The main reason for the formation of solid solution is that the high entropy effect increases the solid solubility between elements and inhibits the formation of intermetallic compounds between metal elements and nitrogen. Because the diffraction peak of the N2:Ar flow ratio of 30:25 is too strong, the diffraction peaks of other N2:Ar flow ratios are not very obvious.

[0077] Test Example 4

[0078] The high entropy alloy nitride film layers (TiAlCrZrWV) N obtained in Examples 1 to 8 were respectively x The cross section was observed by SEM, and the results are as follows Figure 4 Wherein (a) is the high entropy alloy nitride film layer (TiAlCrZrWV) obtained in Example 1 x (b) is a cross-sectional SEM image of the high entropy alloy nitride film (TiAlCrZrWV) obtained in Example 2 x (c) is a cross-sectional SEM image of the high entropy alloy nitride film (TiAlCrZrWV) obtained in Example 3 x(d) is a cross-sectional SEM image of the high entropy alloy nitride film (TiAlCrZrWV) obtained in Example 4 x (e) is a cross-sectional SEM image of the high entropy alloy nitride film (TiAlCrZrWV) obtained in Example 5 x (f) is a cross-sectional SEM image of the high entropy alloy nitride film (TiAlCrZrWV) obtained in Example 6 x (g) is a cross-sectional SEM image of the high entropy alloy nitride film (TiAlCrZrWV) obtained in Example 7 x (h) is a cross-sectional SEM image of the high entropy alloy nitride film (TiAlCrZrWV) obtained in Example 8 x Cross-sectional SEM image.

[0079] Depend on Figure 4 It can be seen that the high entropy alloy nitride film is relatively dense and firmly bonded to the substrate. As the N2:Ar flow ratio increases, the film thickness gradually decreases, which means that the sputtering rate of the high entropy alloy nitride film gradually decreases. The main reason for this phenomenon is the "target poisoning" effect. In addition, from Figure 4 It can be seen that with the increase of N2:Ar flow ratio, the organization of the high entropy alloy nitride film layer becomes more and more dense, which indicates that the addition of nitrogen increases the density of the film layer structure.

[0080] Test Example 5

[0081] For Example 7, the high entropy alloy nitride film layer (TiAlCrZrWV) obtained when N2:Ar=30:25 x The cross section was observed by HRTEM, and the results are as follows Figure 5 As shown. Among them, (a) is the cross-sectional HRTEM image under low magnification, (b) is the cross-sectional HRTEM image under high magnification, and (c) is the selected area electron diffraction image.

[0082] like Figure 5 As shown in (a), it can be seen that the high entropy alloy nitride film is well bonded to the substrate, and from (b), it can be seen that there are nanocrystals (as shown in the A, B, C, and D regions) and amorphous (as shown in the a, b, c, and d regions) in the high entropy alloy nitride film, and the nanocrystals are separated by amorphous, indicating that the high entropy alloy nitride film is composed of a nanocomposite structure. From (c), (111), (200), and (220) can be observed, indicating that the film has an FCC structure, which corresponds to the results shown by XRD.

[0083] Test Example 6

[0084] The high entropy alloy nitride film layers (TiAlCrZrWV) N obtained in Examples 1 to 8 were respectively xThe hardness and elastic modulus were measured. Figure 6 shown.

[0085] Depend on Figure 6 It can be seen that when N2:Ar=0:25, the high entropy alloy nitride film (TiAlCrZrWV) N x The hardness is 13.5GPa and the elastic modulus is 150.2GPa. When the N2:Ar flow ratio is increased to 5:25, the high entropy alloy nitride film (TiAlCrZrWV)N x The hardness increased to 16.4GPa, and the elastic modulus increased to 177.8GPa. With the continued increase of the N2:Ar flow ratio, although the hardness of the high entropy alloy nitride film decreased, it generally showed a trend of first increasing and then decreasing, and the change trend of the elastic modulus was similar to that of the hardness. When N2:Ar=30:25, the hardness of the high entropy alloy nitride film was the best, which was 19.0GPa, and the elastic modulus of the high entropy alloy nitride film was also the best, which was 180.5GPa. Compared with the TiAlCrZrWV alloy film, the hardness and elastic modulus of the high entropy alloy nitride film are significantly improved for the following reasons: First, the formation of saturated metal nitrides increases the hardness. Secondly, the addition of nitrogen leads to an increase in the degree of lattice distortion, thereby producing a strengthening effect. Since the atomic size of nitrogen is different from the atomic size of each metal element, when nitrogen atoms are added to the lattice, severe lattice distortion will be caused, thereby inhibiting dislocation motion and leading to a strengthening effect. In addition, grain size is closely related to mechanical properties. Figure 5 Fine nanocrystals are observed in the HRTEM image of (b). According to the Hall-Petch formula, the finer the grains, the higher the hardness. After that, as the nitrogen flow rate increases further, the surface of the alloy target is prone to generate nitrides due to excessive nitrogen, which may cause the sputtering method to change to direct sputtering of nitrides, thereby reducing its hardness and elastic modulus.

[0086] The high entropy alloy nitride film layers (TiAlCrZrWV) N obtained in Examples 1 to 8 were respectively x Nanoindentation high load toughness test was carried out, and the toughness results obtained were as follows Figure 7 shown.

[0087] Depend on Figure 7 It can be seen that with the increase of nitrogen concentration, the high entropy alloy nitride film (TiAlCrZrWV)N x The fracture toughness value of the high entropy alloy nitride film (TiAlCrZrWV) N x The fracture toughness is 1.15MPa·m 1 / 2 When N2:Ar=20:25, the high entropy alloy nitride film (TiAlCrZrWV)Nx It has the best toughness, with a value of 1.68MPa·m 1 / 2 , which is higher than the toughness of TiAlCrZrWV high entropy alloy film. This shows that the introduction of nitrogen will increase the toughness of the high entropy alloy nitride film, which is mainly because with the increase of nitrogen flow rate, the high entropy alloy nitride film (TiAlCrZrWV)N x The structure of the film changes from an amorphous structure to a nanocomposite structure, and many interfaces of the nanocomposite structure hinder the propagation of cracks. Ultimately, the crack propagation length is significantly shortened, showing the best anti-crack effect, and the fracture toughness of the film is significantly improved.

[0088] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high entropy alloy nitride film, characterized in that: The following steps are involved: Based on TiAlCrZrWV alloy target, a high entropy alloy nitride film layer was prepared on the substrate surface by magnetron sputtering in a nitrogen atmosphere. The flow rate of nitrogen in the nitrogen-containing atmosphere does not exceed 35 sccm.

2. The preparation method according to claim 1, characterized in that: The nitrogen-containing atmosphere is a mixed gas composed of nitrogen and inert gas; the flow ratio of nitrogen to argon in the mixed gas is 0 to 35:

25.

3. The high entropy alloy nitride film layer according to claim 2, characterized in that: The flow ratio of nitrogen to argon in the mixed gas is 0:25, 5:25, 10:25, 15:25, 20:25, 25:25, 30:25 or 35:

25.

4. The preparation method according to claim 1, characterized in that: The molar ratio of each element in the TiAlCrZrWV alloy target is: Ti:Al:Cr:Zr:W:V=1:1:1:1:1:

1.

5. The preparation method according to claim 1, characterized in that: The substrate includes a metal substrate, a cemented carbide substrate, a ceramic substrate or a single crystal silicon substrate.

6. The preparation method according to claim 1, characterized in that: The TiAlCrZrWV alloy target is a DC target; the sputtering power of the magnetron sputtering is 120-190W, the gas pressure is 0.3-1Pa, and the deposition time is 30-90min.

7. The preparation method according to claim 1, characterized in that: Before preparing the high entropy alloy nitride film layer on the substrate surface, the substrate is subjected to ultrasonic treatment and plasma treatment in sequence.

8. The preparation method according to claim 7, characterized in that: The reagent used for the ultrasonic treatment includes at least one of anhydrous ethanol and acetone; the frequency of the ultrasonic treatment is 15 to 30 kHz, and the time is 10 to 20 minutes; the plasma treatment is carried out in an argon atmosphere, and the conditions include: the DC power supply power is 120 to 190 W, the vacuum degree is 2 to 4 Pa, and the time is 5 to 15 minutes.

9. The high entropy alloy nitride film obtained by the preparation method according to any one of claims 1 to 8, characterized in that: Hardness is 18-22GPa, fracture toughness is 1.50-1.90MPa·m 1 / 2 .

10. Use of the high entropy alloy nitride film layer according to claim 9 in a device protective coating.